Electrical Properties of Al2O3 Incorporated CeO2 Thin Films Deposited by RF Magnetron Sputtering. (19th August 2016) - Konishi, Junya; Ohsawa, Takashi; Suzuki, Setsu; Ishibashi, Keiji; Ri, Sung-Gi; Takahashi, Kenichiro; Yamamoto, Yasuhiro
Abstract : The Al2 O3 incorporated CeO2 thin films (Al2 O3 molar fraction of 0.0 to 0.6) were prepared by the RF magnetron sputtering with the combinatorial mask system using the two targets of Al2 O3 and CeO2 in Ar + 10% O2 . The deposited films were annealed in N2 and O2 at 500°C for 30 minutes. The minimum leakage current density of 1.6 x 10 -8 A/cm 2 measured at the electric field of 1MV/cm was obtained for the N2 annealed sample with the Al2 O3 incorporation of 0.2, which value was significantly lower than that of the film without the Al2 O3 incorporation by two orders of magnitude. The variation of the flat band voltage with the incorporated Al2 O3 molar fraction suggested the generation of the fixed positive charge, which was probably arisen from the lower Ce oxide in the film and/or the lower oxide of Si diffused from the substrate into the film.